2012
DOI: 10.1371/journal.pone.0044063
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Characteristics of Bacteremia among Children in Rural Ghana

Abstract: The objective of the study was to describe systemic bacterial infections occurring in acutely ill and hospitalized children in a rural region in Ghana, regarding frequency, incidence, antimicrobial susceptibility patterns and associations with anthropometrical data.Blood cultures were performed in all children below the age of five years, who were admitted to Agogo Presbyterian Hospital (APH), Asante Region, Ghana, between September 2007 and July 2009. Medical history and anthropometrical data were assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(126 citation statements)
references
References 30 publications
5
114
7
Order By: Relevance
“…The infrequent vancomycin dosing strategy often used among hemodialysis-dependent patients may not maintain an adequate trough level in high-flux, large-poresize artificial kidneys (46)(47)(48), increasing the risk for relapsing SAB. Table 1 summarizes the incidences of SAB from the abovementioned studies and other studies (49)(50)(51)(52)(53)(54)(55).…”
Section: Epidemiologymentioning
confidence: 99%
“…The infrequent vancomycin dosing strategy often used among hemodialysis-dependent patients may not maintain an adequate trough level in high-flux, large-poresize artificial kidneys (46)(47)(48), increasing the risk for relapsing SAB. Table 1 summarizes the incidences of SAB from the abovementioned studies and other studies (49)(50)(51)(52)(53)(54)(55).…”
Section: Epidemiologymentioning
confidence: 99%
“…Several other studies have evaluated BSIs at the population level but have had incomplete case ascertainment, have limited analysis to subpopulations, have not specifically defined rates, or have not clearly differentiated between community-and hospital-onset disease (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). It is difficult to precisely define the contemporary (within the last 20 years) overall burden of community-onset BSI, for a number of potential reasons.…”
Section: Overall Populationsmentioning
confidence: 99%
“…Fourth, and perhaps most importantly, these studies were all reported from high-income Western countries. The burden of community-onset disease may be substantially different elsewhere worldwide (12)(13)(14)(15).…”
Section: Overall Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased drug resistance and emergence of new multi-drug resistant S. enterica strains has made iNTS disease difficult to manage [6][7][8]. There is very broad consensus that vaccines against iNTS are urgently needed.…”
Section: Introductionmentioning
confidence: 99%